REPIQUETES AND RISK IN THE CULTIVATION OF RICE IN THE FLOODPLAIN OF THE AMAZON RIVER NEAR IQUITOS, PERU - LIST, Geneva (2019)
The floodplain of the Amazon river offers considerable potential for agriculture but is a risk-filled environment for farmers working the fertile but flood-prone land. Flood reversals that occur as river levels fall and rise between May and November —known as repiquetes— pose a serious threat to crop cultivated on the floodplains, particularly commercial rice. In this paper we analyze the 45-year record of daily water levels at Iquitos to determine the frequency and magnitude of repiquetes and their impact on the crop growing season. Interviews and land surveys conducted in four riverside communities near the Isla Muyuy archipelago indicate the impact of repiquetes and other hazards on rice production, and assessed farmers’ willingness to pay for flood risk adaptation tools. Our findings point to index-based insurance as promising strategy to buffer risk and promote agricultural development of the Amazon floodplain.